Hubungan Pola Konsumsi dan Aktivitas Fisik Dengan Status Gizi Pada Anggota TNI-AD Batalyon Zipur 18/Yudha Karya Raksasa Kabupaten Gianyar - Hapsari, Bella Amanda; Sugiani, Pande Putu Sri; Kusumayanti, Gusti Ayu Dewi (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
The Indonesian National Armed Forces (TNI) is an important component of national defense. One that can affect the performance of the TNI is nutritional status and consumption patterns. TNI has very busy activities in daily activities that require energy. The aim of the study was to determine the relationship between consumption patterns and physical activity with the nutritional status of members of the Indonesian Army Battalion Zipur 18/YKR, Gianyar Regency. This type of observational research uses an approach Cross Sectional with a sample of 42 respondents by means purposive sampling. This research was conducted from January to February 2023. Data collection on consumption patterns was collected using the SQ-FFQ questionnaire.(Semi Quantitative Food Frequency Questionnaire), Physical activity instrument used VO2Max, Nutritional status is determined by BMI criteria. Data is presented with frequency tables and cross tables and then analyzed using tests Chi-square. From the analysis test results Chi-squares hows that there is a relationship between consumption patterns and nutritional status, and there is a relationship between physical activity and nutritional status.